Local economic structure and industry development in Germany (1993-2001) - Uwe Blien; Jens Suedekum (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2005)
This paper analyses the impact of dynamic MAR- and Jacobs-externalities on local employment growth in Germany between 1993 and 2001. In order to facilitate a comparison between the neighbouring countries we firstly replicate the study of Combes (2000) on local employment growth in France and find very similar results for Germany. Afterwards we formulate an alternative empirical model that is based on a weighted regression approach. With this model we find that Jacobs-externalities matter in manufacturing, whereas MAR-externalities are present in advanced service sectors.
Keywords: R11; O40; 330; Wirtschaftswachstum - Auswirkungen; Beschäftigungsentwicklung; regionale Disparität; Regionalentwicklung; regionale Faktoren; Regionales Wachstum; Beschäftigungseffekt; Lokalisationseffekt; Regionale Entwicklung; Wissenstransfer; Schätzung; Deutschland